2020
DOI: 10.1038/s41437-020-0308-x
|View full text |Cite
|
Sign up to set email alerts
|

Larger bacterial populations evolve heavier fitness trade-offs and undergo greater ecological specialization

Abstract: Evolutionary studies over the last several decades have invoked fitness trade-offs to explain why species prefer some environments to others. However, the effects of population size on trade-offs and ecological specialization remain largely unknown. To complicate matters, trade-offs themselves have been visualized in multiple ways in the literature. Thus, it is not clear how population size can affect the various aspects of trade-offs. To address these issues, we conducted experimental evolution with Escherich… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 84 publications
5
25
0
Order By: Relevance
“…Although directional selection may promote multiple mutants that affect similar fitness-relevant phenotypes in the evolution condition, each mutant could have disparate latent phenotypic effects that do not contribute immediately to fitness. When the environment changes, these disparate phenotypic effects may be revealed, imposing fitness costs of different magnitudes or allowing for diverse solutions to a variety of possible new environments ( Bono et al, 2017 ; Chavhan et al, 2020 ; Jerison et al, 2020 ; Li et al, 2019 ). This latent phenotypic complexity also has the potential to alter the future adaptive paths that a population takes even in a constant environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although directional selection may promote multiple mutants that affect similar fitness-relevant phenotypes in the evolution condition, each mutant could have disparate latent phenotypic effects that do not contribute immediately to fitness. When the environment changes, these disparate phenotypic effects may be revealed, imposing fitness costs of different magnitudes or allowing for diverse solutions to a variety of possible new environments ( Bono et al, 2017 ; Chavhan et al, 2020 ; Jerison et al, 2020 ; Li et al, 2019 ). This latent phenotypic complexity also has the potential to alter the future adaptive paths that a population takes even in a constant environment.…”
Section: Discussionmentioning
confidence: 99%
“…A yeast evolution experiment across eight environments showed a general pattern of specialization, but not necessarily trade-offs (Jerison et al 2020); analysis of replicate populations showed a large role for stochastic forces in evolution. Chavhan et al (2020) provide an empirical example in which costs of adaptation increase with population size, underlining the point that trade-offs are an outcome of evolutionary processes as well as a determinant of their course. Replicate experiments that yield trade-offs sometimes but not always are expected if possible mutations vary in their degree of antagonistic pleiotropy (Bono et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evolution methods have a long history of application to this question (Kassen 2002;Bono et al 2020), and continue to help uncover complex variation in these costs. For example, costs have been observed to be greater in larger populations (Chavhan et al 2020), highly variable across replicate experiments (Jerison et al 2020), or to appear late in adaptation (Satterwhite & Cooper 2015). In the field, reciprocal transplant experiments with plant and animal species reveal highly variable costs of adaptation with only a weak signal of trade-offs (Hereford 2009).…”
Section: Introductionmentioning
confidence: 99%